Address challenges law schools face with an innovative dean. Issue 10 (June 2015) - Hope, Joan
<x xml:space="preserve">Abstract</x> Few areas of the academy are changing more quickly than the law school. To lead the school through changes that help it thrive, the school needs a dean with the skills, connections and ideas to innovate.